Propostas de pagamento no estudo de matemática financeira : análise de uma abordagem prática - Francisco, Marcelo Sabbadini (Universidade Federal de São Carlos, 2017)
The objective of the project and research was to apply and conjecture about a practical approach to the study of payment methods, using commercial proposals of students' daily routine of a technical course in the management area. Assessing the historical and conceptual aspects, as well as associating them to students' daily life, in order to assist the student and the technical future in their future commercial transactions, whether private or professional, and enable them to conceptually and critically evaluate the methods of payment offered in the acquisition of a property, were the main strands developed in the application of the research proposal, as recommended by various scholars in the area of financial education, among them GRANDO and SCHNEIDER (2011). The work was developed, according to the theoretical presuppositions of didactic engineering, in stages, among them the study of conceptual and historical aspects of the amortization system, analysis of everyday situations and the application of questionnaires. The researcher professor conducted the study in the 1st module of technical course in finances at a state technical school in Jaú city. The results obtained in the questionnaires from the students finances course were compared with the results from the students in the first module of the management technical course. However in the management class the content was developed by exposing the theory and solving problem situations. The guiding question for our research was: “Does a practical approach to the study of financing systems help the student by comparing the methods of payment opt for the most economical option?” The analysis of the results presented a favorable framework for the proposal of a practical approach, prioritizing the use of everyday situations, to the study of payment methods besides it offered a more critical learning to the detriment of a reproductive bias normally observed in the teaching of financial mathematics.
Keywords: Matemática financeira; Formas de pagamento; Sistemas de amortização; Educação financeira; Financial mathematics; Forms of payment; Amortization systems; Financial education; CIENCIAS EXATAS E DA TERRA::MATEMATICA